A tunable 0.86‐3.83 GHz bandpass filter with high selectivity. Issue 4 (3rd January 2020) - Wang, Xian; Zhang, Dewei; Liu, Qing; Lv, Dalong; Zhang, Yi; Yang, Songtao
Abstract: This letter presents a tunable bandpass filter (BPF) with wide tuning range of center frequency and high selectivity. The wide frequency tuning range is achieved by two pairs of switchable varactors‐tuned parallel coupled line resonators with direct‐feed structure, which can be switched to lower and higher frequency resonator modes by using p‐i‐n diodes. Since the electromagnetic mixed coupling and frequency‐variant source‐load coupling are incorporated in this configuration, three self‐adaptive transmission zeros (TZs) close to the tunable passband are obtained. Also, three TZs can almost keep the same relative location of passband to achieve continuous high selectivity and good out‐of‐band rejection over the whole frequency tuning range. Meanwhile, by selecting a proper coupling region, a constant fractional bandwidth (CFBW) in the frequency tuning process can be realized. For verification, a tunable 0.86‐3.83 GHz BPF with a 12% CFBW and high selectivity is designed, fabricated and measured. The experimental results show the proposed filter has the advantages of wide tuning range and high selectivity.